FRI0418 How important is the assessment of asdas in the long-term evaluation of disease activity in ankylosing spondylitis? a comparison with currently used clinical parameters. (23rd January 2014) - Baraliakos, X.; Fritz, C.; Listing, J.; Haibel, H.; Sieper, J.; Braun, J.
Abstract : Background: Measures for disease activity (BASDAI) or response to therapy (ASAS partial remission (PR)) are widely used in the assessment of patients with ankylosing spondylitis (AS). The recently developed ASDAS is a composite score, which includes clinical measures and CRP and has a high discriminatory capacity for assessing disease activity. However, only little is known about the course of ASDAS as compared to all other clinical assessments in the long-term outcome of patients with AS. Objectives: In this study we compare the performance of ASDAS-CRP vs. the BASDAI and ASAS outcomes in assessing and predicting clinical response in AS patients under longterm TNF-blocker therapy. Methods: Initially, 69 patients were included in this first study of anti-TNF treatment with infliximab in AS, of whom 43 (63.2%) finished the 3 rd, 42/69 (60.9%) the 5 th and 29 (42.2%) the 10 th study year (y). Low disease activity status was measured by the BASDAI (<3 units) and was compared to the ASDAS definition of low disease activity (<2.1 units), while for clinical response, the ASAS-PR was compared to ASDAS inactive disease status (ASDAS <1.3) at different time points over the 10y of follow-up. Results: There was significant decrease in both ASDAS (BL: 4.3±0.8, 3y: 1.5±0.9, 5y: 1.6±1.0, 10y: 1.7±1.0) and BASDAI (BL: 6.4±1.4, 3y: 2.4±1.9, 5y: 2.4±2.0, 10: 2.7±2.0). Overall, a BASDAI <3 was achieved by 19/29 (65.5%), 18/29 patients (62.1%), and 17/29 patients (58.6%), while ASDAS <2.1 was achieved by 23/29 (79.3%), 20/29 (69%) and 19/29 (65.5%) patients at 3y, 5y and 10y, respectively. In comparison, ASAS-PR was found in 10/29 (34.5%) at 3y and 5y and in 5/29 (17.2%) patients at 10y while ASDAS<1.3 was found in 13/29 (44.8%) at 3y and in 12/29 (41.4%) at 5y and 10y. Clinical outcome after 12 weeks of treatment was a significant predictor for achieving ASAS-PR over the 10 years of the study: for each unit of decreasing in BASDAI status at week 12, achievement of ASAS-PR at 10y increased with an OR [95% CI] of 3.64 [1.17–11.20] (p=0.025), while the OR for each unit of decreasing in ASDAS status at week 12 in order to reach ASAS-PR at 10y was 4.76 [1.20–18.90] (p=0.027). Similar results were found for ASDAS inactive disease at the end of year 10: for each unit of decreasing in ASDAS status at week 12, achievement of ASDAS inactive disease at 10y increased with an OR [95% CI] of 2.20 [1.00–4.86] (p=0.05), while the OR for each unit of decreasing in BASDAI status at week 12 in order to reach ASDAS inactive disease at 10y was 1.64 [1.05–2.58] (p=0.029). Conclusions: The long-term course of BASDAI and ASDAS showed similar magnitude of improvement. Interestingly the clinical outcome after 12 weeks of treatment was a significant predictor of the outcome at the end of year 10. The significant decrease of ASAS-PR rates after 10 years can be explained by the inclusion of functional assessments (BASFI) in this measure, which are not included in the ASDAS. The higher discriminative value of ASDAS in comparison to other widely used measurements needs to be considered in clinical trials but also daily practice for assessment of long-term outcomes in patient with AS. Disclosure of Interest: None Declared